Modelling of p-tyramine transport across human intestinal epithelial cells predicts the presence of additional transporters - Sarkar, Shreyasi; Saika-Voivod, Ivan; Berry, Mark D. (Frontiers in Physiology, 2022)
p-Tyramine (TYR) is an endogenous trace amine, which can also be synthesized by intestinal microbiota, and is present in commonly consumed diets. TYR is an agonist for the intracellular trace amine-associated receptor 1, which has been implicated in psychiatric, metabolic, and immune-related disorders. We have previously demonstrated TYR readily diffuses across lipid bilayers, while transport across Caco-2 cell membranes involves Organic Cation Transporter 2 (OCT2) and a Na+-dependent active transporter. Here we developed mathematical models to determine whether known kinetics for these processes are sufficient to explain observed transcellular TYR passage. Ordinary differential equations were developed for known TYR transport processes to predict concentration-time relationships. Michaelis-Menten kinetics were assumed for all transporter-mediated processes and a one phase exponential function used for simple diffusion. Modelled concentration-time plots were compared to published experimental results. Additional transporter functions were sequentially added to models to improve consistency, and a least squares error minimization approach utilized to determine added transporter kinetics. Finally, possible TYR compartmentalization was also modelled. Following apical loading, transport across the apical, but not the basolateral, membrane was modelled without additional transporters, suggesting a basolateral transporter was missing. Consistent with this, models of basolateral compartment loading did not match experimental observations, indicating missing basolateral transporters were bidirectional. Addition of a transporter with the kinetic characteristics of OCT2 did not improve models. Varying the kinetic parameters of the added transporter improved models of basolateral, but worsened apical, loading models, suggesting the need for either a directional preference in transporters, or intracellular TYR compartmentalization. Experimental parameters were recapitulated by introducing asymmetry into the apical OCT2 (Kt_OCT2_apicaltocell = 110.4 nM, Kt_OCT2_celltoapical = 1227.9 nM), and a symmetric basolateral facilitated diffusion transporter (Vmax = 6.0 nM/s, Kt = 628.3 nM). The apparent directionality of OCT2 may reflect altered TYR ionization due to known pH differences between compartments. TYR compartmentalization only partially replaced the need for asymmetry of OCT2. In conclusion, modelling indicates that known TYR transport processes are insufficient to explain experimental concentration-time profiles and that asymmetry of the apical membrane OCT2 combined with additional, low affinity, basolateral membrane facilitated diffusion transporters are required.